2021
DOI: 10.1523/jneurosci.2600-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin B-Expressing Neurons of the Central Extended Amygdala Mediate Inhibitory Synaptic Input onto Melanin-Concentrating Hormone Neuron Subpopulations

Abstract: The lateral hypothalamic area (LHA) is a highly conserved brain region critical for maintaining physiological homeostasis and goal-directed behavior. LHA neurons that express melanin-concentrating hormone (MCH) are key regulators of arousal, energy balance, and motivated behavior. However, cellular and functional diversity among LHAMCHneurons is not well understood. Previous anatomic and molecular data suggest that LHAMCHneurons may be parsed into at least two distinct subpopulations, one of which is enriched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 139 publications
(229 reference statements)
6
14
0
Order By: Relevance
“…Our findings extended those by Fujita and colleagues (2021) who noted that Pmch cells may express at least two electrical fingerprints, but these two fingerprints were not exclusively correlated to Carpt and Tacr3 coexpression. Interestingly, we noted that Tacr3 expression may be higher than the expression of its corresponding protein NK3R.…”
Section: Electrophysiology: Electrical Fingerprint Of Mch Cells Varie...supporting
confidence: 89%
See 3 more Smart Citations
“…Our findings extended those by Fujita and colleagues (2021) who noted that Pmch cells may express at least two electrical fingerprints, but these two fingerprints were not exclusively correlated to Carpt and Tacr3 coexpression. Interestingly, we noted that Tacr3 expression may be higher than the expression of its corresponding protein NK3R.…”
Section: Electrophysiology: Electrical Fingerprint Of Mch Cells Varie...supporting
confidence: 89%
“…Interestingly, NK3R expression defined another subset of MCH cells, as NK3R was almost exclusively seen in MCH/CART+ cells, and only a few MCH cells expressed NK3R in the absence of CART. This is consistent with single-cell RNAseq analysis (Mickelsen et al, 2019; Fujita et al, 2021) revealing that Pmch cells can be divided into two major subclusters: one that strongly expressed both Carpt and Tacr3 , the genes for CART and NK3R respectively, and one that was Cartpt - and Tacr3 -negative. Furthermore, Cartpt and Tacr3 have also been recognized as highly expressed genes in Pmch cells by other RNAseq datasets like HypoMap (Steuernagel et al, 2022).…”
Section: Neuroanatomy: Mapping Cart and Nk3r Expression In Hypothalam...supporting
confidence: 88%
See 2 more Smart Citations
“…In the CeA, Tac2 -expressing neurons mainly modulate consolidation of fear memory (Andero et al ., 2014; Florido et al, 2021). A recent study showed that Tac2 -expressing neurons in the BNST and the CeA regulate behavioral states, i.e., emotional valence, by sending inhibitory inputs to the LHA neurons expressing melanin-concentrating hormone (Fujita et al, 2021). These studies suggest that Tac2 -expressing neurons are uniquely positioned in specific brain regions to modulate behavioral homeostasis.…”
Section: Discussionmentioning
confidence: 99%